Conductive film

CN115699219BActive Publication Date: 2026-10-27NITTO DENKO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180037118.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-05-22
Filing Date
2021-05-18
Publication Date
2026-10-27
Estimated Expiration
2041-05-18

AI Technical Summary

Technical Problem

然而,形成有金属氧化物层的导电性膜存在弯曲性不充分的问题

Benefits of technology

[0014]根据本发明,能够提供一种导电性膜,其是在包含金属纳米线的透明导电层上形成金属膜而构成的导电性膜,且在供于蚀刻工序时导电性也不易降低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115699219B_ABST
    Figure CN115699219B_ABST
Patent Text Reader

Abstract

Provided is a conductive film that is a conductive film configured by forming a metal film on a transparent conductive layer containing metal nanowires, and in which the conductivity is not easily reduced when subjected to an etching process. The conductive film of the present invention successively has a metal layer, a transparent conductive layer, and a substrate, the transparent conductive layer contains metal nanowires and a polymer matrix, a portion of the metal nanowires protrudes from the transparent conductive layer toward the metal layer side, and the thickness of the transparent conductive layer is 30 nm to 150 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to conductive films. Background Technology

[0002] Previously, conductive films used as electrodes in touch sensors were mostly conductive films with metal oxide layers such as indium-tin oxide (ITO) layers formed on resin films. However, conductive films with metal oxide layers have insufficient flexibility. As a conductive film with excellent flexibility, a conductive film having a transparent conductive layer containing metal nanowires using silver, copper, etc., has been proposed.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Publication No. 2009-505358 Summary of the Invention

[0006] The problem the invention aims to solve

[0007] In a conductive film having a transparent conductive layer containing metal nanowires as described above, narrow wiring can be achieved by forming a metal film on the transparent conductive layer and patterning using photolithography. However, during the etching of the metal film in this photolithography process, there is a problem that the metal nanowires are corroded, resulting in a decrease in the conductivity of the conductive film.

[0008] The present invention was made to solve the above-mentioned problems, and its purpose is to provide a conductive film, which is a conductive film formed by forming a metal film on a transparent conductive layer containing metal nanowires, and whose conductivity is not easily reduced during the etching process.

[0009] means for solving problems

[0010] The conductive film of the present invention comprises a metal layer, a transparent conductive layer, and a substrate in sequence. The transparent conductive layer includes metal nanowires and a polymer matrix. A portion of the metal nanowires protrudes from the transparent conductive layer toward the metal layer side. The thickness of the transparent conductive layer is 30 nm to 150 nm.

[0011] In one embodiment, the thickness of the transparent conductive layer is 30 nm to 120 nm.

[0012] In one embodiment, the substrate is composed of a cycloolefin resin.

[0013] Invention Effects

[0014] According to the present invention, a conductive film can be provided, which is a conductive film formed by forming a metal film on a transparent conductive layer containing metal nanowires, and whose conductivity is not easily reduced during the etching process. Attached Figure Description

[0015] Figure 1 This is a schematic cross-sectional view of a conductive film according to one embodiment of the present invention. Detailed Implementation

[0016] A. Overall composition of the conductive film

[0017] Figure 1 This is a schematic cross-sectional view of a conductive film according to one embodiment of the present invention. The conductive film 100 sequentially comprises a metal layer 10, a transparent conductive layer 20, and a substrate 30. The transparent conductive layer 20 includes metal nanowires 21 and a polymer matrix 22. A portion of the metal nanowires 21 protrudes from the transparent conductive layer 20 toward the metal layer 10. Although not shown, the conductive film may further comprise any suitable other layers.

[0018] In this invention, the thickness of the transparent conductive layer is 30 nm to 150 nm. This thickness is equivalent to the thickness of the aforementioned polymer matrix. By forming the transparent conductive layer at this thickness, the surface conductivity of the transparent conductive layer can be well ensured while effectively protecting the metal nanowires and preventing their corrosion. In particular, this invention is useful in preventing corrosion of the metal nanowires even when a portion of the metal layer is removed by chemical methods such as etching. The prevention of metal nanowire corrosion results in a conductive film with a narrow wiring pattern exhibiting excellent conductivity. In one embodiment, the conductive film (essentially a transparent conductive layer) of this invention is corrosion-resistant to aqueous solutions containing one or more of the following: sulfuric acid, hydrogen peroxide solution, hydrochloric acid, copper chloride, and ferric chloride. When exposed to such aqueous solutions, the rate of change (rate of increase) of the surface resistivity is also less than 20%.

[0019] The surface resistivity of the conductive film of the present invention is preferably 0.01Ω / □ to 1000Ω / □, more preferably 0.1Ω / □ to 500Ω / □, particularly preferably 0.1Ω / □ to 300Ω / □, and most preferably 0.1Ω / □ to 100Ω / □.

[0020] The rate of increase in surface resistivity of the conductive film after immersion in the metal layer etching solution for 5 minutes is preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, and particularly preferably 5% or less. The above-mentioned rate of increase in surface resistivity is calculated by the resistance value of (resistance value after immersion / resistance value before immersion - 1) × 100.

[0021] The thickness of the conductive film of the present invention is preferably 10 μm to 500 μm, more preferably 15 μm to 300 μm, and even more preferably 20 μm to 200 μm.

[0022] B. Metal layer

[0023] The aforementioned metal layer is composed of a conductive metal. Examples of metals constituting the metal layer include copper, silver, aluminum, nickel alloys, copper alloys, titanium alloys, and silver alloys. Copper is preferred.

[0024] The thickness of the aforementioned metal layer is preferably 10–1000 nm, more preferably 50–300 nm.

[0025] Any suitable method can be used as a method for forming the aforementioned metal layer. Examples of methods for forming the metal layer include: vapor phase film formation methods represented by vacuum evaporation and sputtering, and wet methods represented by electroplating or electroless plating.

[0026] C. Transparent conductive layer

[0027] As described above, the transparent conductive layer comprises metal nanowires and a polymer matrix.

[0028] As described above, the thickness of the transparent conductive layer is 30 nm to 150 nm, preferably 30 nm to 140 nm, more preferably 30 nm to 130 nm, and particularly preferably 30 nm to 120 nm. In one embodiment, the thickness of the transparent conductive layer is preferably 55 nm to 150 nm, more preferably 55 nm to 140 nm, further preferably 60 nm to 130 nm, and particularly preferably 65 nm to 120 nm. When the thickness falls within the range described above, the aforementioned effects of the present invention become significant. Furthermore, when the transparent conductive layer is thinner than 30 nm, there is a possibility that the metal nanowires are not adequately protected, and corrosion of the metal nanowires cannot be prevented. Additionally, when the transparent conductive layer is thicker than 150 nm, there is a possibility that surface conductivity cannot be adequately ensured.

[0029] In one embodiment, the transparent conductive layer is patterned. As a patterning method, any suitable method can be used depending on the shape of the transparent conductive layer. The pattern shape of the transparent conductive layer can be any suitable shape depending on the application. Examples include the patterns described in Japanese Patent Application Publication No. 2011-511357, Japanese Patent Application Publication No. 2010-164938, Japanese Patent Application Publication No. 2008-310550, Japanese Patent Application Publication No. 2003-511799, and Japanese Patent Application Publication No. 2010-541109. After the transparent conductive layer is formed on the substrate, it can be patterned using any suitable method according to the shape of the transparent conductive layer.

[0030] The total light transmittance of the aforementioned transparent conductive layer is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more.

[0031] The aforementioned metal nanowires refer to conductive materials made of metal, shaped like needles or filaments, and with a diameter of nanometers. Metal nanowires can be straight or curved. If a transparent conductive layer composed of metal nanowires is used, the metal nanowires become mesh-like. Thus, even a small amount of metal nanowires can form good conductive paths, resulting in a conductive film with low resistance.

[0032] The ratio of the thickness d to the length L of the aforementioned metal nanowires (aspect ratio: L / d) is preferably 10 to 100,000, more preferably 50 to 100,000, and particularly preferably 100 to 10,000. Using metal nanowires with such a large aspect ratio allows for good interlacing, resulting in high conductivity with a small amount of metal nanowires. This leads to a transparent conductive layer with high light transmittance. Furthermore, in this specification, "thickness of the metal nanowire" refers to its diameter when the cross-section of the metal nanowire is circular, its minor axis when the cross-section is elliptical, and its longest diagonal when the cross-section is polygonal. The thickness and length of the metal nanowires can be confirmed using a scanning electron microscope or a transmission electron microscope.

[0033] The thickness of the aforementioned metal nanowires is preferably less than 500 nm, more preferably less than 200 nm, particularly preferably 10 nm to 100 nm, and most preferably 10 nm to 60 nm. Within this range, a transparent conductive layer with high light transmittance can be formed.

[0034] The length of the aforementioned metal nanowires is preferably 1 μm to 1000 μm, more preferably 1 μm to 500 μm, and particularly preferably 1 μm to 100 μm. Within this range, a conductive film with high conductivity can be obtained.

[0035] As the metal constituting the above-mentioned metal nanowires, any suitable metal can be used, as long as it has high conductivity. Examples of metals constituting the above-mentioned metal nanowires include silver, gold, copper, and nickel. In addition, materials obtained by plating these metals (e.g., gold plating) can also be used. The metal nanowires are preferably composed of one or more metals selected from gold, platinum, silver, and copper.

[0036] Any suitable method can be used as a method for manufacturing the aforementioned metal nanowires. Examples include: reducing silver nitrate in solution; and continuously forming metal nanowires by applying an external voltage or current to the precursor surface from the tip of a probe and pulling out the metal nanowire using the tip of the probe. In the method of reducing silver nitrate in solution, silver nanowires can be synthesized by liquid-phase reduction of silver salts such as silver nitrate in the presence of polyols such as ethylene glycol and polyvinylpyrrolidone. Uniformly sized silver nanowires can be mass-produced, for example, according to the methods described in Xia, Y. et al., Chem. Mater. (2002), 14, 4736-4745, and Xia, Y. et al., Nano letters (2003) 3(7), 955-960.

[0037] Regarding the proportion of metal nanowires in the aforementioned transparent conductive layer, relative to the total weight of the transparent conductive layer, it is preferably 30% to 100% by weight, more preferably 30% to 90% by weight, and even more preferably 45% to 80% by weight. If it falls within this range, a transparent conductive layer with excellent conductivity and light transmittance can be obtained.

[0038] Any suitable polymer can be used as the polymer constituting the polymer matrix described above. Examples of such polymers include: acrylic polymers; polyester polymers such as polyethylene terephthalate; aromatic polymers such as polystyrene, polyvinyl toluene, polyvinyl xylene, polyimide, polyamide, and polyamide-imide; polyurethane polymers; epoxy polymers; polyolefin polymers; acrylonitrile-butadiene-styrene copolymer (ABS); cellulose; silicone polymers; polyvinyl chloride; polyacetate; polynorbornene; synthetic rubber; and fluorinated polymers. Preferably, a curable resin (preferably a UV-curable resin) composed of polyfunctional acrylates such as pentaerythritol triacrylate (PETA), neopentyl glycol diacrylate (NPGDA), dipentaerythritol hexaacrylate (DPHA), dipentaerythritol pentaacrylate (DPPA), and trimethylolpropane triacrylate (TMPTA) is used.

[0039] The density of the transparent conductive layer is preferably 1.3 g / cm³. 3 ~10.5g / cm 3 More preferably 1.5 g / cm³ 3 ~3.0g / cm 3 If this range is met, a transparent conductive layer with excellent conductivity and light transmittance can be obtained.

[0040] A transparent conductive layer can be formed by coating a conductive layer forming composition containing metal nanowires onto a substrate (or a laminate of the substrate and other layers) and then drying the coating.

[0041] In addition to metal nanowires, the above-mentioned conductive layer forming composition may also contain any suitable solvent. The conductive layer forming composition can be prepared in the form of a dispersion of metal nanowires. Examples of such solvents include water, alcohol-based solvents, ketone-based solvents, ether-based solvents, hydrocarbon-based solvents, and aromatic solvents. From the viewpoint of reducing environmental impact, water is preferred. The above-mentioned conductive layer forming composition may further contain any suitable additives depending on the purpose. Examples of such additives include corrosion inhibitors to prevent corrosion of metal nanowires and surfactants to prevent aggregation of metal nanowires. The type, quantity, and amount of additives used can be appropriately determined according to the purpose.

[0042] When the aforementioned transparent conductive layer contains a polymer matrix, the polymer matrix can be formed as follows: after coating and drying the conductive layer forming composition as described above, a polymer solution (polymer composition, monomer composition) is coated onto a layer composed of metal nanowires, and then the polymer solution coating layer is dried or cured to form the transparent conductive layer. Alternatively, a conductive layer forming composition containing a polymer constituting the polymer matrix can also be used to form the transparent conductive layer.

[0043] The dispersion concentration of the metal nanowires in the above-mentioned conductive layer forming composition is preferably 0.1% to 1% by weight. If this range is met, a transparent conductive layer with excellent conductivity and light transmittance can be formed.

[0044] As a coating method for the above-mentioned conductive layer forming composition, any suitable method can be used. Examples of coating methods include: spray coating, rod coating, roller coating, die coating, inkjet coating, screen coating, dip coating, letterpress printing, gravure printing, photogravure printing, etc. As a drying method for the coated layer, any suitable drying method can be used (e.g., natural drying, air drying, heat drying). For example, in heat drying, the drying temperature is typically 50°C to 200°C, preferably 80°C to 150°C. The drying time is typically 1 to 10 minutes.

[0045] The polymer solution described above contains the polymer constituting the polymer matrix, or the precursor of the polymer (monomer constituting the polymer).

[0046] The polymer solution described above may contain a solvent. Examples of solvents included in the polymer solution include: alcohol solvents, ketone solvents, tetrahydrofuran, hydrocarbon solvents, or aromatic solvents. Preferably, the solvent is volatile. The boiling point of the solvent is preferably below 200°C, more preferably below 150°C, and even more preferably below 100°C.

[0047] D. Substrate

[0048] The aforementioned substrate is typically composed of any suitable resin. Examples of resins constituting the substrate include: cyclic olefin resins, polyimide resins, polyvinylidene chloride resins, polyvinyl chloride resins, polyethylene terephthalate resins, and polyethylene naphthalate resins. Cyclic olefin resins are preferred. Using a substrate composed of a cyclic olefin resin results in a conductive film with excellent flexibility.

[0049] As a cyclic olefin resin, polynorbornene is preferred, for example. Polynorbornene refers to a (co)polymer obtained by using part or all of a norbornene monomer having a norbornene ring as a starting material (monomer). Various products of the aforementioned polynorbornene are commercially available. Specific examples include: ZEONEX and ZEONOR manufactured by Zeon Corporation of Japan, Arton manufactured by JSR Corporation, TOPAS manufactured by TICNA Corporation, and APEL manufactured by Mitsui Chemicals Corporation.

[0050] The glass transition temperature of the resin constituting the above-mentioned substrate is preferably 50°C to 200°C, more preferably 60°C to 180°C, and even more preferably 70°C to 160°C. A substrate having a glass transition temperature within this range can prevent deterioration during the formation of the transparent conductive layer.

[0051] The thickness of the above-mentioned substrate is preferably 8μm to 500μm, more preferably 10μm to 250μm, even more preferably 10μm to 150μm, and particularly preferably 15μm to 100μm.

[0052] The total light transmittance of the aforementioned substrate is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. Within this range, a conductive film preferably used as a conductive film in touch panels and the like can be obtained.

[0053] The aforementioned substrate may further contain any suitable additives as needed. Specific examples of additives include: plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, UV absorbers, flame retardants, colorants, antistatic agents, compatibilizers, crosslinking agents, and thickeners. The types and amounts of additives used can be appropriately determined according to the purpose.

[0054] Various surface treatments can be applied to the above-mentioned substrate as needed. Surface treatments can be performed using any suitable method depending on the purpose. Examples include: low-pressure plasma treatment, ultraviolet irradiation treatment, corona treatment, flame treatment, and acid or alkali treatment. In one embodiment, the transparent substrate is surface-treated to make its surface hydrophilic. If the substrate is made hydrophilic, the processability is excellent when coating a composition for forming a transparent conductive layer prepared using an aqueous solvent. Furthermore, a conductive film with excellent adhesion between the substrate and the transparent conductive layer can be obtained.

[0055] [Example]

[0056] The present invention will now be specifically described through examples, but the present invention is not limited to these examples in any way. The evaluation methods in the examples and comparative examples are described below.

[0057] (1) Rate of increase in resistance value

[0058] Regarding the resistance value of the conductive film, the initial resistance value (R0) was measured using the eddy current method with a non-contact surface resistance meter manufactured by Napson Corporation, under the trade name "EC-80". Subsequently, the conductive film was immersed in a metal layer etching solution at room temperature for 5 minutes, followed by drying at room temperature for 30 minutes, and the resistance value (R) was measured again. The rate of increase in resistance value R / R0 was calculated from the initial resistance value (R0) and the resistance value (R).

[0059] (2) Surface conductivity

[0060] The two ends of a conductive film (50mm×50mm) with a metal film formed on a transparent conductive layer are masked by 10mm. The metal layer is then removed. The conductivity of the metal layer at both ends is then confirmed by a testing machine. If it can conduct, it is evaluated as OK; if it cannot conduct, it is evaluated as NG.

[0061] [Manufacturing Example 1]

[0062] (Manufacturing of metal nanowires)

[0063] Add 5 ml of anhydrous ethylene glycol and an anhydrous ethylene glycol solution of PtCl2 (concentration: 1.5 × 10⁻⁶) to a reaction vessel equipped with a stirrer at 160°C. -40.5 ml of anhydrous ethylene glycol solution of AgNO3 (concentration: 0.12 mol / L) and 5 ml of anhydrous ethylene glycol solution of polyvinylpyrrolidone (MW: 55000) (concentration: 0.36 mol / L) were added dropwise to the obtained solution after 4 minutes and 6 minutes. Following this addition, the solution was heated to 160°C and reacted for more than 1 hour until AgNO3 was completely reduced, generating silver nanowires. Then, acetone was added to the reaction mixture containing silver nanowires obtained in the above manner until the volume of the reaction mixture increased fivefold. The reaction mixture was then centrifuged (2000 rpm, 20 minutes) to obtain silver nanowires. The silver nanowires (concentration: 0.2 wt%) and pentaethylene glycol dodecyl ether (concentration: 0.1 wt%) were dispersed in pure water to prepare a silver nanowire dispersion.

[0064] [Example 1]

[0065] (Preparation of the composition (PN) for forming a transparent conductive layer)

[0066] A transparent conductive layer forming composition (PN) with a solid content concentration of 0.05% by weight was prepared by diluting the above-mentioned silver nanowire dispersion with 25 parts by weight and 75 parts by weight of pure water.

[0067] (Preparation of monomer composition a)

[0068] A monomer composition with a solid content of 1% by weight was obtained by diluting 80 parts by weight of isopropanol, 1 part by weight of pentaerythritol triacrylate (manufactured by Osaka Organic Chemicals Co., Ltd., trade name "Viscoat#300"), and 0.2 parts by weight of photopolymerization initiator (manufactured by BASF, trade name "Irgacure 907") with diacetone alcohol and 19 parts by weight of isopropanol.

[0069] (Fabrication of conductive films)

[0070] The above-mentioned transparent conductive layer forming composition (PN) is coated on one side of a substrate (polycyclic olefin film (manufactured by Zeon Corporation of Japan, trade name "ZEONOR (registered trademark)", thickness 25 μm) and dried. Then, the above-mentioned monomer composition is coated on the transparent conductive layer forming composition (PN) coating layer, dried at 90°C for 1 minute, and subsequently irradiated with 300 mJ / cm². 2 Ultraviolet light is used to form a transparent conductive layer (thickness: 55nm).

[0071] Subsequently, a copper-containing metal layer is formed on the transparent conductive layer by sputtering.

[0072] The conductive film was obtained in accordance with the above method. The obtained conductive film was subjected to the above evaluation (1) and (2). The results are shown in Table 1.

[0073] [Example 2]

[0074] The thickness of the transparent conductive layer was set to 90 nm, and the conductive film was otherwise obtained in the same manner as in Example 1. The obtained conductive film was used for the evaluations (1) and (2) described above. The results are shown in Table 1.

[0075] [Example 3]

[0076] The thickness of the transparent conductive layer was set to 130 nm, and the conductive film was otherwise obtained in the same manner as in Example 1. The obtained conductive film was subjected to the evaluations (1) and (2) described above. The results are shown in Table 1.

[0077] [Example 4]

[0078] (Preparation of monomer composition b)

[0079] A monomer composition with a solid content of 1% by weight was obtained by diluting 1 part by weight of urethane acrylate (manufactured by DIC, trade name "LUXYDIR 17-806") and 0.2 parts by weight of photopolymerization initiator (manufactured by BASF, trade name "Irgacure 907") with 80 parts by weight of isopropanol and 19 parts by weight of diacetone alcohol.

[0080] (Fabrication of conductive films)

[0081] Monomer composition b was used instead of monomer composition a, and the thickness of the transparent conductive layer was set to 90 nm. Otherwise, the conductive film was obtained in the same manner as in Example 1. The obtained conductive film was subjected to the above evaluations (1) and (2). The results are shown in Table 1.

[0082] [Comparative Example 1]

[0083] The thickness of the transparent conductive layer was set to 200 nm, and otherwise the conductive film was obtained in the same manner as in Example 1.

[0084] [Comparative Example 2]

[0085] The uncoated monomer composition forms a transparent conductive layer without a polymer matrix, otherwise a conductive film is obtained in the same manner as in Example 1.

[0086] [Table 1]

[0087]

[0088] Symbol Explanation

[0089] 10 Metal Layers

[0090] 20 Transparent conductive layer

[0091] 30 Substrate

[0092] 100 conductive film

Claims

1. A conductive film comprising, in sequence, a metal layer, a transparent conductive layer, and a substrate, The metal layer is composed of copper, silver, aluminum, nickel alloy, copper alloy, titanium alloy, or silver alloy. The transparent conductive layer comprises metal nanowires and a polymer matrix. A portion of the metal nanowire protrudes from the transparent conductive layer toward the metal layer side. The thickness of the transparent conductive layer is 60nm to 130nm. The proportion of the metal nanowires in the transparent conductive layer is 45% to 80% by weight relative to the total weight of the transparent conductive layer.

2. The conductive film according to claim 1, wherein, The substrate is composed of a cyclic olefin resin.

Citation Information

Patent Citations

  • A flexible and transparent contact detection system for electronic devices

    JP2003511799A

  • Capacitance input device

    JP2008310550A

  • Transparent conductors based on nanowires

    JP2009505358A

  • Touch screen panel

    JP2010164938A

  • Single-layer touch-sensitive display

    JP2010541109A